The Use Of Adjuvant Therapies For Tonsillectomy - Hassan, Hussein M. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: The aim was to ascertain the current practice of adjuvant therapy for tonsillectomy and to determine whether it is evidence based. Methods: A questionnaire answers were obtained from sixty otolaryngologists in Baghdad. Results: There was no any enthusiasm for routine intra-operative local anaesthesia. Paracetamol (Acetaminophen) is prescribed by nearly all surgeons for postoperative analgesia, and the current literature supports its efficacy and safety. Further, some practitioners combine paracetamol with NSAIDs, and/or Tramadol-Opioids. Evidence to support the additional use of these agents is, however non existent or limited. For the use of antibiotics, we found some of the otolaryngologists do use a course of few days of pre-operative antibiotics and almost all of them do give postoperative antibiotics for seven-ten days. Some aspects of tonsillectomy care are uniform and evidence based. Others are heterogenous and suffer from lack of adequate data in the literature.